Creating multipoint-to-point LSPs for traffic engineering. - Bhatnagar, Sudeept (IEEE Communications magazine)
Traffic engineering enhances an ISP's capability to manage and utilize its resources effectively. MPLS has emerged as an efficient packet forwarding tool that gives a significant boost to the traffic engineering capabilities of an ISP. A fundamental problem in MPLS is to reduce label space usage by label switched paths while meeting the requirements of the flows traversing the network. Using multipoint-to-point LSP trees has been proposed as one of the techniques to reduce label space usage. We look at the problem of creating multipoint-to-point LSPs given a set of precomputed point-to-point LSPs. We propose a heuristic for multipoint-to-point LSP creation and show its effectiveness.